GMP-Compliant Manufacturing of TRUCKs: CAR T Cells targeting GD2 and Releasing Inducible IL-18 - Glienke, Wolfgang; Dragon, Anna Christina; Zimmermann, Katharina; Martyniszyn-Eiben, Alexandra; Mertens, Mira; Abken, Hinrich; Rossig, Claudia; Altvater, Bianca; Aleksandrova, Krasimira; Arseniev, Lubomir; Kloth, Christina; Stamopoulou, Andriana; et al. (Frontiers in Immunology, 2022)
Chimeric antigen receptor (CAR)-engineered T cells can be highly effective in the treatment of hematological malignancies, but mostly fail in the treatment of solid tumors. Thus, approaches using 4th advanced CAR T cells secreting immunomodulatory cytokines upon CAR signaling, known as TRUCKs (“T cells redirected for universal cytokine-mediated killing”), are currently under investigation. Based on our previous development and validation of automated and closed processing for GMP-compliant manufacturing of CAR T cells, we here present the proof of feasibility for translation of this method to TRUCKs. We generated IL-18-secreting TRUCKs targeting the tumor antigen GD2 using the CliniMACS Prodigy® system using a recently described “all-in-one” lentiviral vector combining constitutive anti-GD2 CAR expression and inducible IL-18. Starting with 0.84 x 108 and 0.91 x 108 T cells after enrichment of CD4+ and CD8+ we reached 68.3-fold and 71.4 fold T cell expansion rates, respectively, in two independent runs. Transduction efficiencies of 77.7% and 55.1% was obtained, and yields of 4.5 x 109 and 3.6 x 109 engineered T cells from the two donors, respectively, within 12 days. Preclinical characterization demonstrated antigen-specific GD2-CAR mediated activation after co-cultivation with GD2-expressing target cells. The functional capacities of the clinical-scale manufactured TRUCKs were similar to TRUCKs generated in laboratory-scale and were not impeded by cryopreservation. IL-18 TRUCKs were activated in an antigen-specific manner by co-cultivation with GD2-expressing target cells indicated by an increased expression of activation markers (e.g. CD25, CD69) on both CD4+ and CD8+ T cells and an enhanced release of pro-inflammatory cytokines and cytolytic mediators (e.g. IL-2, granzyme B, IFN-γ, perforin, TNF-α). Manufactured TRUCKs showed a specific cytotoxicity towards GD2-expressing target cells indicated by lactate dehydrogenase (LDH) release, a decrease of target cell numbers, microscopic detection of cytotoxic clusters and detachment of target cells in real-time impedance measurements (xCELLigence). Following antigen-specific CAR activation of TRUCKs, CAR-triggered release IL-18 was induced, and the cytokine was biologically active, as demonstrated in migration assays revealing specific attraction of monocytes and NK cells by supernatants of TRUCKs co-cultured with GD2-expressing target cells. In conclusion, GMP-compliant manufacturing of TRUCKs is feasible and delivers high quality T cell products.